Association between human gut microbiota and obesity according to Body Mass Index - Valdivia, Alejandra V. (2024)
Investigation about the gut microbiota as a tool to address obesity is a promising field. The influence of the microbiota on the endocrine system and host metabolism is crucial to understanding how it can affect body weight. For this review, relevant keywords such as "gut microbiota and obesity", "gut microbiota and BMI" and "gut microbiota composition" were used in the article search. 50 articles in English and Spanish were identified, of which 15 were selected that met the established inclusion criteria. Comparative studies that analyse the gut microbiota in groups of individuals from different regions of the world, according to their BMI classification, are especially valuable. 16S rRNA sequencing technology, based on the analysis of faecal samples, has consistently demonstrated a significant association between gut microbiota composition and BMI. Although specific bacteria that directly contribute to obesity have not yet been identified, certain predominant types have been observed in populations with this condition. Importantly, the types of bacteria associated with obesity can vary between studies, although predominant patterns can be identified in each BMI classification, particularly among lean and obese individuals. In the Peruvian context, the lack of studies on the association between the composition of the gut microbiome and obesity represents a significant opportunity. Future research in Peru could provide fundamental data to develop effective strategies for the prevention and treatment of obesity in the local population.